Nigella sativa Extract Increases Antibacterial Activity by Up-Regulating T-reg and Th2 Levels in Salmonella enterica subsp. enterica serovars Typhimurium-Exposed Balb/c Mice - Zahra Ahmed; Sumarno Reto Prawiro; Agustina Tri Endharti (Research Journal of Life Science, 2018)
Nigella sativa extract (NSE) is known to be an effective antibacterial and immuno-modulating agent. This study aimed to demonstrate that treatment of Salmonella eterica subsp. eterica serovars typhimurium-infected mice with NSE would cause an increase in T-regulatory (T-reg) and Th2 cells and a decrease in the number of spleen bacterial colonies. Mice were randomly divided into five groups [control (T0), mice infected with S. typhimurium only (T1), and mice infected with S. typhimurium and then treated with NSE 0.52, 5.2, or 52 mg/kg body weight NSE (N1, N2, and N3, respectively)]. Levels of T-reg and Th2 cells were determined via flow cytometry and the number of spleen bacterial colonies was determined by observation. The results showed that treatment with NSE 0.52, 5.2, and 52 mg/kg significantly increased the number of T-reg and Th2 cells (p<0.05) relative to T0. Administration of NSE 5.2 mg/kg increased the number of T-reg cells, while administration of NSE 52 mg/kg caused the greatest increase in the number of Th2 cells in the spleens of S. typhimurium-infected mice. Moreover, no S. typhimurium colonies were found in the spleens of any NSE-treated mice. Our results suggest that NSE has therapeutic potential to ameliorate S. typhimurium infection.